A prospective, multicentre, cohort study to assess the incidence of dengue illness in households from selected communities in Brazil (2014–2018). (July 2021) - de Aguiar, Daniele Fernandes; de Barros, Eliana Nogueira C; Ribeiro, Guilherme Sousa; Brasil, Patricia; Mourao, Maria Paula Gomes; Luz, Kleber; Aoki, Francisco Hideo; Freitas, Andre Ricardo Ribas; Calvet, Guilherme Amaral; Oliveira, Eduardo; Branco, Bianca F; Abreu, Ariane; et al.
Highlights: This was a prospective surveillance study of dengue in Brazil from 2014 to 2018. Dengue seroprevalence was 76%; 23% of participants reported dengue history. Incidence of laboratory-confirmed symptomatic infection was 6.1/1000 person-years. For each symptomatic infection, there were ∼7 inapparent primary dengue infections. Study highlights underestimation of dengue infection in Brazil. Abstract: Objectives: To estimate the incidence of dengue infection across geographically distinct areas of Brazil. Methods: This prospective, household-based, cohort study enrolled participants in five areas and followed them up for up to 4 years (2014–2018). Dengue seroprevalence was assessed at each scheduled visit. Suspected dengue cases were identified through enhanced passive and active surveillance. Acute symptomatic dengue infection was confirmed through reverse-transcriptase quantitative polymerase chain reaction in combination with an antigenic assay (non-structural protein 1) and serology. Results: Among 3300 participants enrolled, baseline seroprevalence was 76.2%, although only 23.3% of participants reported a history of dengue. Of 1284 suspected symptomatic dengue cases detected, 50 (3.9%) were laboratory-confirmed. Based on 8166.5 person-years (PY) of follow-up, the incidence of laboratory-confirmed symptomatic infection (primary endpoint) was 6.1 per 1000 PY (95% confidence interval [CI]: 4.5, 8.1). Incidence varied substantially in different years (1.8–7.4 per 1000 PY). The incidence of inapparent primary dengue infection was substantially higher: 41.7 per 1000 PY (95% CI: 31.1, 54.6). Conclusions: Our findings, highlighting that the incidence of dengue infection is underestimated in Brazil, will inform the design and implementation of future dengue vaccine trials. Clinical trial registration: NCT01751139